KUALITAS VISUAL DAN REPRESENTASI FOTO MAKANAN KULINER BANDUNG DI INSTAGRAM - Irma Rochmawati (Universitas Komputer Indonesia, 2018)
Food photography is now becoming popular in the form of online photo sharing through social media Instagram. The phenomenon of photography using the camera on mobile device and spread to social media Instagram produce different visual quality and representations, especially to the object of food. In this research also discussed the development of food photography from the birth of photographic technology (non-photo technique), the technological change from mechanical to digital photography, until the born of Instagram photographic technology in food photography and share it widely to social media. This study aims to find out the causes and the factors that affected of the differences in the visual quality and representation of food photography that spread in Instagram. By using descriptive qualitative method through observation of food photography spread on Instagram, analyzes each food photograph that were examined from visual elements, should be able to represent the reality of the food object or not. Results from the study indicate that there are differences in visual quality and representation of the food photography spread in social media Instagram in case study of Bandung Culinary. The visual quality of photography determined by the quality of camera and capability of the photographer (maker) in photographic techniques. The Visualization of food photography can not fully represent the reality, because it involves not only the sense of sight (visual) but also involve other sense, such as auditory. Through a good understanding, expecting the designers and photographers of food can be more precise in making design decisions including the selection of the visual elements because they already know the impact of generated representation.